MEMPERTIMBANGKAN MODEL DIALOG STRATEGIS DALAM MEMBANGUN SISTEM DAFTAR PEMILIH TETAP (DPT) YANG LEBIH BAIK* - Ryan Saputra Alam; Saiful Wathan (Journal of Governance and Administrative Issues, 2022)
The chaotic occurrence of permanent voter lists (DPT) in several general elections (elections) must be handled by implementing an integrated and integrated e-Government. Based on the literature study, it can be concluded that the electronic DPT has been built only based on a narrow view of E-Government, which only seems to be a collection of hardware, software, data, and procedures. It takes a strategy in the form of a strategic dialogue model that emphasizes the central role of humans and humanity, which is one of the keys to the successful implementation of MIS in the E-Government.